The Effect of Digital Innovation through Duolingo and Artificial Intelligence on English Language Learning Outcomes - Elida, Yusti; Oktadela, Resy; Hadiyanti, Putri Octa; Yuliani, Sri; Ganisa, Ratu (Journal of English Language and Education, 2025)
This study investigates the effect of Duolingo, an AI-enhanced mobile learning platform, on English language learning outcomes among sixth-grade students at Sekolah Dasar Islam Terpadu (SDIT) Imam Syafii Cendikia, Pekanbaru. Despite the growing integration of digital technologies in Indonesian secondary and higher education, the application of AI-based platforms in Islamic elementary schools remains limited. This research addresses this gap by examining how adaptive, gamified learning tools can enhance linguistic achievement while maintaining alignment with Islamic educational values. A one-group pretest-posttest quasi-experimental design was employed with 30 participants over six weeks. Results indicated significant improvement in English proficiency, with mean scores increasing from 62.47 (SD = 10.42) to 81.63 (SD = 7.91), yielding a large effect size (Cohen's d = 0.88). Questionnaire data revealed highly positive student perceptions (M = 4.36, SD = 0.52) regarding motivation, usability, and attitudes toward AI-based learning. Classroom observations confirmed high engagement levels (M = 4.32) across attention, participation, and collaborative behavior. The findings suggest that AI-driven adaptive learning platforms can effectively personalize instruction, reduce achievement gaps, and foster intrinsic motivation in mixed-ability classrooms when culturally contextualized within faith-based pedagogy. This study contributes empirical evidence supporting the integration of AI-assisted language learning in Indonesian Islamic elementary education.